2002
DOI: 10.1111/j.1530-0277.2002.tb02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Is Associated With Enrichment of High‐Density Lipoprotein Particles in Polyunsaturated Lipids and Increased Cholesterol Esterification Rate

Abstract: Regular wine consumption is associated with high levels of polyunsaturated lipids in HDL and with increases in the cholesterol esterification rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…10 Recently it has been suggested that alcohol or a metabolite may inhibit the glycosylation of CETP, which could affect the binding of CETP to lipoproteins in alcohol drinkers. 26 Other metabolic pathways that may also play a role in the association between alcohol and HDL-C concentration include increased transport rate of apolipoproteins, reduced hepatic lipase activity, and greater lecithin cholesterol acyl transferase activity 27,28 and a combination of all may be the most likely scenario. 29 -31 Consistent with our findings, other observational studies have found that genetic variation in CETP influences the association between alcohol consumption and HDL-C, such that the highest HDL-C concentrations are found among B2 carriers who drink alcohol.…”
Section: Alcohol Cholesteryl Ester Transfer Protein and High-density ...mentioning
confidence: 99%
“…10 Recently it has been suggested that alcohol or a metabolite may inhibit the glycosylation of CETP, which could affect the binding of CETP to lipoproteins in alcohol drinkers. 26 Other metabolic pathways that may also play a role in the association between alcohol and HDL-C concentration include increased transport rate of apolipoproteins, reduced hepatic lipase activity, and greater lecithin cholesterol acyl transferase activity 27,28 and a combination of all may be the most likely scenario. 29 -31 Consistent with our findings, other observational studies have found that genetic variation in CETP influences the association between alcohol consumption and HDL-C, such that the highest HDL-C concentrations are found among B2 carriers who drink alcohol.…”
Section: Alcohol Cholesteryl Ester Transfer Protein and High-density ...mentioning
confidence: 99%
“…Although there is no doubt that wine, especially red wine, exhibits antioxidant properties owing to its content of polyphenols,6–13 the properties of wine in terms of regulating cholesterol metabolism are not well known. Only a few studies have concluded that moderate consumption of red wine increases production of high‐density lipoprotein (HDL) cholesterol and, possibly, plasminogen, tissue plasminogen factor and endothelial function and decreases platelet aggregation, fibrinogen and lipoprotein(a) 1, 18. In this sense the present paper provides new data on whether moderate wine consumption is able to regulate or not cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…While the antioxidant properties of polyphenolic compounds in red wine appear to be the cause of its beneficial effects on coronary heart disease, some other properties have also been discussed. Thus moderate alcohol consumption increases production of high‐density lipoprotein (HDL) cholesterol and, possibly, plasminogen, tissue plasminogen factor and endothelial function and decreases platelet aggregation, fibrinogen, and lipoprotein(a) 1, 18. In the present work we studied the effect of various sherries on serum levels of HDL cholesterol following their administration to rats over a sustained period and found increased serum HDL cholesterol and decreased total cholesterol levels.…”
Section: Introductionmentioning
confidence: 76%
“…High levels of HDL cholesterol are associated with low risks of cardiovascular morbidity and mortality. HDL cholesterol rises with the consumption of alcohol (7,37,46,47). Epidemiological studies have shown that those who consume alcohol moderately develop lower LDL cholesterol levels.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…This antioxidant effect is believed to be a result of both plasma urate levels and polyphenols (50). Wine polyphenols decrease platelet aggregation and adhesion to endothelium, increase HDL cholesterol independent of the alcohol content of wine and inhibit the oxidation of LDL cholesterol (24,(51)(52)(53)(54). These compounds inhibit the cyclo-oxygenase and lipo-oxygenase of platelets and macrophages, thereby inhibiting clotting and the inflammatory mediators in a developing atheroma.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%